Hypertrophic Obstructive Cardiomyopathy with Severe Aortic Valve Stenosis – A Case Report of a Commonly Overlooked Dual Pathology - Khadka, Pralaya; Rajbanshi, Bijoy G; Hirachan, Anish; Gautam, Milan; KC, Sangam; Sharma, Ranjit; Neupane, Prabesh; Baidhya, Sajan (Nepalese Heart Journal, 2025)
We report a case of coexisting hypertrophic obstructive cardiomyopathy and aortic stenosis in a 69-year-old female who presented with exertional breathlessness and palpitations. Trans thoracic echocardiogram revealed severe valvular aortic stenosis and asymmetric septal hypertrophy with obstruction and mild to moderate mitral valve stenosis. The patient underwent concurrent aortic valve replacement with a tissue valve and extended septal myectomy. Post-surgery, the patient experienced significant symptom relief and improved functional status with no residual obstruction in the left ventricular outflow tract. This case highlights the necessity of assessing for sub-valvar obstruction while assessing valvular aortic stenosis.